Brief Mindfulness-Based Interventions in a Laboratory Context: a Systematic Review of Randomized Controlled Trials. - Jiménez Jiménez, Oliver; Ramos-Díaz, Natalia Sylvia; González-Moraleda, Álvaro; Resurrección, Davinia M. (My University, 2020)
Objectives. Brief mindfulness-based interventions conducted in laboratory context have increased in recent years as a novel form of intervention. However, there are no reports of their association with improved psychological health. The main objective of the present study was to systematically review the evidence from randomized controlled trials in a laboratory context of the relationship between brief mindfulness interventions and psychological outcomes. Methods. MEDLINE, Scopus, Open Gray, Psycinfo, Web of Science, Proquest, and the Cochrane Database were searched for relevant publications from inception to March 2019. Search terms included (a) brief mindfulness, and (b) laboratory setting. Results. A total of 4799 studies were reviewed, 19 of which were finally included, only three conducted in a clinical population. All the included studies were from the last decade. A total of 19 psychological variables were included, among which are anxiety, positive affect or distress. The studies differ in the type of intervention, the duration of the intervention and the type of variable studied. Conclusions. Brief mindfulness interventions need to be examined with greater rigor in their application. In order to reach relevant conclusions regarding their implementation, consensus must be reached regarding the type of intervention, settings, timing and target population.
Keywords: Mente; Psicología - Investigación; Brief Mindfulness; Laboratory Setting; Psychological Wellbeing; Systematic Review